ROLE JUST IN TIME METHOD FOR EFFORTS TO ELIMINATE NON-VALUE ADDED ACTIVITY IN PRODUCTION GARMENT COMPANY VOXI 73 - Kantjai, Silvana; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The concept of cost effectiveness or known as the manufacturing cycle effectiveness (MCE) is the ratio between the processing time to the cycle time.This research is to identify the extent to which the benefits and role of Just In Time (JIT) Method for eliminating all activities or resources that are not value-added and to give an idea of ​​the importance of the implementation of Just In Time for companies to improve efficiency and productivity. This research using a Garment Company "VOXI 73" Pandaan is in JalanJuanda 2 PandaanPasuruan Malang – Surabaya as a object. By using a JIT method this research found that Company make a wasting in several indicator. This is evidenced by the amount of non-value added time which consists of the top set-up time, move time, waiting time, and inspection time in throughput time. After using the JIT system efficiency of processing time becomes 93.93% means non-value added time by only 6.07%. With the efficiency that it creates a huge cost savings.advice to companies, along with the progress of science and technology is so rapid, and the increasing levels of competition among companies that are very tight, so that each managment is required to be able to compete and organize an effective strategy in the global competition. Keywords: just in time, production, garment